Modern advanced accounting - Larsen, E. John. (New York : McGraw-Hill, 1991)
The book reflects the continuing changes that have been occurring in the development of accounting principles and practice, with special attention to the official pronouncements and exposure drafts of the Financial Accounting Standards Board.
Includes bibliographical references and index.
occ 17/01/2019
Loans
Keywords: Accounting